Role of a specific member of 235 kDa multigene family (Py235) of the rodent malaria parasite Plasmodium yoelii in parasite mediated virulence - Bapat, Devaki Dinesh (2011)
The mechanism by which the invasive form of the malaria parasites, the merozoite, selects and successfully invades an erythrocyte involves numerous receptor-ligand interactions. Recognition of specific erythrocyte receptor by the merozoite is mediated by at least two gene families: the Reticulocyte binding protein Homologues (RHs) and the Erythrocyte Binding Ligands (EBLs). In the rodent malaria parasite Plasmodium yoelii, members of the RHs termed Py235 (Plasmodium yoelii 235 kDa rhoptry protein) are implicated in host cell selection and invasion. In P. yoelii, Py235 as well as a single member of EBL have been shown to be key mediators of virulence enabling the parasite to invade a wider range of host erythrocytes. Previous studies using both quantitative RT-PCR and mass spectrometry have identified Py01365 as the dominant Py235 member expressed in the virulent P. yoelii YM strain. Based on these findings, py01365 was disrupted and its overall impact on parasite virulence and Py235 expression levels was investigated. We found that disruption of py01365 (PYΔpy01365) resulted in significantly lower parasitaemias, increased host cell selectivity and longer survival of the host, identifying this member of Py235 as a key mediator of virulence in the virulent P. yoelii YM strain. Moreover, the analysis of the impact of the disruption of py01365 on the transcription levels of the other py235 members showed no significant change in the overall py235 transcription pattern in PYΔpy01365 as compared to YM. We observed that the protective mcAb 25.77, which had recently been shown to recognize Py01365, reacted specifically with a large number of schizonts in the PYΔpy01365 by Immunofluorescence microscopy, suggesting that mcAb 25.77 was still able to recognize other members of Py235.